Kajian Teori Konsep Healing Environment sebagai Strategi Desain pada Pusat Rehabilitasi Anak Terlantar - Ukhtiya Muthiah; Sri Yuliani; Bambang Triratma (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The strategy for designing a rehabilitation center for abandoned children needs to pay attention to several criteria based on the characteristics of neglected children. The design criteria are arranged to get psychological comfort so that children can grow up with more productive activities, one of which can be through the application of the concept of a healing environment. The research aims to examine the theory of healing environment that fits the criteria of a rehabilitation center for neglected children as the basis for a design strategy. The research uses qualitative methods with comparative study techniques and theoretical reference comparisons. The result of the research is a design strategy based on the concept of healing environment which combines indoor and outdoor elements by exploiting the potential of the tropical climate related to natural lighting and ventilation.